Greening trade and investment : environmental protection without protectionism - Neumayer, Eric (Earthscan Pub. LondonGB, 2001)
Shows ways in which the multilateral investment and trade regimes could be made more environmentally friendly without unnecessarily restricting the free flow of capital and goods and services. Indicates also, how it can be done without detriment to the economic development aspirations of developing countries.